2011
DOI: 10.1084/jem.20110434
|View full text |Cite
|
Sign up to set email alerts
|

Th17 lymphocytes traffic to the central nervous system independently of α4 integrin expression during EAE

Abstract: Th1 lymphocytes preferentially infiltrate into the spinal cord during EAE via a VLA-4–mediated mechanism while Th17 lymphocyte infiltration is dependent on LFA-1 expression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
249
4
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 232 publications
(281 citation statements)
references
References 67 publications
25
249
4
3
Order By: Relevance
“…The blockade of VLA-4 did not block Th17 cells to infiltrate the brain, expressing both IL-23R and CCR6. Accordingly, T cell-conditional 4-deficient mice were not resistant to actively induced EAE but showed an ataxic syndrome with predominantly supraspinal infiltrates of T cells (Rothhammer V 2011). Corroborating this idea, it was previously showed that Th17 cells constitutively express the chemokine receptor CCR6, whose ligand, CCL20 is also constitutively expressed by choroid plexus cells.…”
Section: Self-tolerancementioning
confidence: 94%
“…The blockade of VLA-4 did not block Th17 cells to infiltrate the brain, expressing both IL-23R and CCR6. Accordingly, T cell-conditional 4-deficient mice were not resistant to actively induced EAE but showed an ataxic syndrome with predominantly supraspinal infiltrates of T cells (Rothhammer V 2011). Corroborating this idea, it was previously showed that Th17 cells constitutively express the chemokine receptor CCR6, whose ligand, CCL20 is also constitutively expressed by choroid plexus cells.…”
Section: Self-tolerancementioning
confidence: 94%
“…While Th1 cells critically rely on α4-integrins, Th17 cells can cross the brain barriers in an α4-integrin-independent manner and enter the CNS [22,23]. We next investigated if presence or absence of PSGL-1 has any influence in the polarization of our PLP-specific T-cell lines into Th1, Th17, or Th2 cells.…”
Section: Establishment Of Effector Memory Wt and Psgl-1 −/− Sjl/j T-cmentioning
confidence: 99%
“…It has been previously shown that IVIg interferes with leukocyte recruitment to the CNS in an a4 integrin-dependent manner (24). However, Th17 and Th1 cells use different strategies to invade the CNS (25,26). To investigate the effect of IVIg on trafficking of Th17 and Th1 in EAE, brain and spinal cords were analyzed on the day of onset (day 9).…”
Section: Ivig Decreases Infiltration Of Lymphocytes To the Cns By Inhmentioning
confidence: 99%